Landasan Filsafat Pendidikan dalam Perbandingan Sistem Pendidikan Finlandia dan Indonesia - Amelia Yustina Fatmawati; Ekoh Saikoh; Sholeh Hidayat (STKIP Subang, 2025)
Education systems across countries are shaped by underlying philosophical foundations that guide policy formulation, curriculum design, learning processes, and teacher professionalism. This study aims to compare the philosophical foundations of education in Finland and Indonesia by examining their ontological, epistemological, and axiological principles. Using a qualitative-comparative design, data were analyzed through document review of official educational policies, curriculum frameworks, and recent scholarly studies. The findings show that Finland’s education system is rooted in humanism, constructivism, and egalitarianism, which prioritize learner autonomy, trust-based professionalism, and equity. Meanwhile, Indonesia’s educational philosophy integrates perennialism, progressivism, and socio-religious values, leading to an emphasis on character education, national identity, and standardized learning. These philosophical orientations contribute to differences in curriculum organization, assessment practices, and teacher governance. The study concludes that Indonesia can strengthen its system by adopting Finland’s trust-based professionalism and reduced assessment pressure while still maintaining local philosophical values.